The Influence of Selected Antecedents of Frontline Employee 's Perceptions of Service Recovery Performance - Ardahan, M. Güven (1. Fiu Hospitality Review and 2. Flu School of Hospitality and Tourism Management, 2007)
The purpose of this study is to determine the potential impact of selected organizational factors on boundary spanning-role employees’ perceptions of service recovery performance. This study also aims to assess the impact of service recovery performance on the intention to leave the job and extrinsic job satisfaction. This study uses a sample of front line employees in Belek, Antalya, Turkey. The empirical findings revealed that education, team work and role ambiguity as frontline job perceptions were found to exert positive influences on the service recovery performance, but, empowerment, reward, and organizational commitment were found to have negative effects on the service recovery performance.
The file in this item is the publisher version (published version) of the article.
Keywords: Emplyee Percemtion; Turkey; Empowerment; Service; Job Satisfaction